The Portuguese Restoration of 1640 and Its Global Visualization : Political Iconography and Transcultural Negotiation - Krass, Urte (Book collections on Project MUSE.)
The Portuguese Restoration of 1640 ended the dynastic union of Portugal and Spain. This book pioneers in reconstructing the global image discourse related to the event by bringing together visualizations from three decades and four continents. These include paintings, engravings, a statue, coins, emblems, miniatures, a miraculous crosier and other regalia, buildings, textiles, a castrum doloris, drawings, and ivory statues. Situated within the academic field of visual studies, the book interrogates the role of images and depictions before, during, and after the overthrow and how they functioned within the intercontinental communication processes in the Portuguese Empire. The results challenge the conventional notion of center and periphery and reveal unforeseen entanglements as well as an unexpected agency of imagery from the remotest regions under Portuguese control. The book breaks new ground in linking the field of early modern political iconography with transcultural art history and visual studies.